General Perception of Doctor–Patient Relationship From Patients During the COVID-19 Pandemic in China: A Cross-Sectional Study - Zhou, Yanan; Chen, Shubao; Liao, Yanhui; Wu, Qiuxia; Ma, Yuejiao; Wang, Dongfang; Wang, Xuyi; Li, Manyun; Wang, Yunfei; Wang, Yingying; Liu, Yueheng; Liu, Tieqiao; et al. (Frontiers in Public Health, 2021)
The doctor-patient relationship (DPR) is essential for many outcomes in medical consultations. Poor DPR will lead to poor medical outcomes, medical violence, and a negative perception of the healthcare system. On the one hand, there are limited studies on how DPR is affected during the novel coronavirus disease 2019 (COVID-19) pandemic, especially in China. This study aimed to explore DPR during the COVID-19 pandemic. Participants were recruited during the pandemic via convenience and snowball sampling. They were given several questionnaires, including the Patient-doctor relationship questionnaire (PDRQ-9), Chinese Wake Forest Physician Trust Scale (C-WFPTS), a survey on medical violence, factors that affect and improve DPR, and general trust in medical services to complete online. Results revealed that trust in medical services generally increased after the pandemic, and participants thought that the public had a higher increase in trust than themselves. In addition, self-employed, institutional staff, and other professionals had lower trust in doctors than non-medical students. Finally, public awareness, such as medical education, communication, and better medical infrastructure such as medical services, technology, and legislation are essential factors that affect and improve DPR. These results signify the importance of DPR for medical consultations and public health policies during a public health crisis.